Forskningsintegritet og videnskabens etos: – om redeskideri og ansvarlig forskningspraksis - Dige, Morten (Tidsskrift for Professionsstudier, 2021)
In this article, I discuss present development in Danish university research, which put research integrity under pressure. The background for the article is a recent enhanced focus on the subject in the shape of rules and procedures for enhancing responsible conduct of research. The article discusses the relation between norms and counter norms for scientific research and includes a recent case about questionable research practice at Aarhus University.